芝麻素对调和油煎炸稳定性的影响Effect of sesamin on frying stability of blend oil - 张天宇1，魏学鼎1，王澍2，何东平1,2,3，雷芬芬1,3，周力1,3 ZHANG Tianyu1, WEI Xueding1, WANG Shu2, HE Dongping1,2,3, LEI Fenfen1,3, ZHOU Li1,3 (Zhongguo youzhi)
为促进芝麻素作为天然抗氧化剂在煎炸油中的应用，考察了芝麻素对调和油煎炸稳定性的影响。将未添加抗氧化剂的大豆油、棕榈油、葵花籽油、菜籽油按照一定比例调配制得调和油，并以其中的大豆油为对照分别添加0.02%的芝麻素、0.05%的天然维生素E（VE）和0.02%的特丁基对苯二酚（TBHQ），进行32 h的连续煎炸试验，分析煎炸过程中油样酸值、极性组分含量、碘值、过氧化值和脂肪酸组成的变化。结果表明：随着煎炸时间的延长，所有煎炸油的酸值、极性组分含量均增加，碘值均降低，未添加抗氧化剂的空白油样的过氧化值增加，添加抗氧化剂油样的过氧化值则呈先升高后降低再升高趋势；添加抗氧化剂可有效抑制油样酸值和过氧化值的升高和碘值的降低，总体来看TBHQ的效果最好，芝麻素次之，VE效果较差；随着煎炸时间的延长，煎炸油的不饱和脂肪酸含量降低，饱和脂肪酸含量升高，不饱和脂肪酸含量变化幅度大小顺序为空白油样＞添加VE油样＞添加芝麻素油样＞添加TBHQ油样，相对于大豆油，调和油的不饱和脂肪酸含量变化较小；总体来看，调和油的反式脂肪酸含量低于大豆油。综上，芝麻素可以提高煎炸油的氧化稳定性，其效果介于TBHQ和VE之间。 To promote the application of sesamin as a natural antioxidant in frying oil, the effect of sesamin on the frying stability of blend oil was investigated. Blend oil was prepared by blending soybean oil, palm oil, sunflower seed oil and rapeseed oil without antioxidants in a certain proportion. The soybean oil was used as the control, and 0.02% sesamin, 0.05% natural vitamin E (VE) and 0.02% TBHQ were added to the soybean oil and the blend oil respectively. A continuous frying experiment was conducted for 32 h, and the changes in acid value, polar component content, iodine value, peroxide value and fatty acid composition of the oil samples during frying were analyzed. The results showed that with the prolonging of frying time, the acid value and polar component content of the frying oils increased, the iodine value decreased, and the peroxide value of the blank oil samples without antioxidants increased, while the peroxide value of the oil samples with antioxidants added first increased, then decreased and then increased. The addition of antioxidants could effectively inhibit the increase of acid value and peroxide value, and the decrease of iodine value of the oil samples, among which TBHQ had the best effect, followed by sesamin, and VE had the poorest effect. With the prolonging of frying time, the content of unsaturated fatty acids in the frying oils decreased, and the content of saturated fatty acids increased. The change range of unsaturated fatty acids was blank oil samples > oil samples with VE added > oil samples with sesamin added > oil samples with TBHQ added, and compared with soybean oil samples, the change of unsaturated fatty acids in blend oil samples was smaller. In general, the content of trans fatty acids in blend oil samples was lower than that in soybean oil samples. In conclusion, sesamin can improve the oxidation stability of frying oil, and its effect is between TBHQ and VE.